2012
DOI: 10.1161/circep.111.966358
|View full text |Cite
|
Sign up to set email alerts
|

Vectorcardiography as a Tool for Easy Optimization of Cardiac Resynchronization Therapy in Canine Left Bundle Branch Block Hearts

Abstract: In patients with left bundle branch block (LBBB) and heart failure, cardiac resynchronization therapy (CRT) aims to accomplish a more synchronous ventricular electric activation and contraction pattern by left ventricular (LV) based pacing, thereby improving LV systolic function. Clinical Perspective on p 552In applying CRT, optimizing the atrioventricular (AV) delay is important, because it determines the coupling between atrial and ventricular contraction, the dyssynchrony between the right ventricle (RV) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 19 publications
(20 reference statements)
2
16
1
Order By: Relevance
“…15,18 The present study also supports our earlier data that ENDO BiVP is to be favored over conventionally applied EPI BiVP with respect to indices of electrical dyssynchrony and pump function. 10 The relative increase in QRS width by Vernakalant and Flecainide observed in the present study is comparable with that in the previously reported studies that have FIGURE 2.…”
Section: Electrophysiological Effectssupporting
confidence: 90%
“…15,18 The present study also supports our earlier data that ENDO BiVP is to be favored over conventionally applied EPI BiVP with respect to indices of electrical dyssynchrony and pump function. 10 The relative increase in QRS width by Vernakalant and Flecainide observed in the present study is comparable with that in the previously reported studies that have FIGURE 2.…”
Section: Electrophysiological Effectssupporting
confidence: 90%
“…The optimal LVdP/dt max consistently occurred at an interval where ATV epi and VA QRS were at values halfway between those during LBBB and LV pacing, supporting data from a previous study. 13 During AV optimization, the average interval offset was 2±11 ms for VA QRS and −9±24 ms for ATV epi (P=N.S. for both comparisons).…”
Section: Hemodynamic Effects Of Pacingmentioning
confidence: 90%
“…13 The VA QRS value halfway from LBBB and LV pacing at a short AV interval has been shown to predict maximal contractility response during AV/VV optimization. 13 For cardiac mapping electrograms, local depolarization times were calculated as the time difference between onset of the Q-wave (during baseline) or ventricular pacing artifact and the time of steepest negative deflection. Using custom MATLAB software (MathWorks, Natick, MA), the depolarization times were plotted on corresponding anatomic locations and on matched interpolated models.…”
Section: Measurements Of Vectorcardiography Electric Activation Andmentioning
confidence: 99%
“…In the canine model of LBBB, the amplitude of the QRS vector was found to be the electrical equivalent of mechanical dyssynchrony. 152 The QRS vector amplitude value halfway between intrinsic LBBB and fully captured LV pacing predicted the atrioventricular and interventricular delay of largest haemodynamic response. 152 Electrocardiographic optimization of CRT, therefore, might replace the need for separate echocardiographic and haemodynamic equipment and would substantially decrease the variability that affects haemodynamic measurements.…”
Section: Importance Of the Percentage Of Pacingmentioning
confidence: 96%